2008
DOI: 10.3923/pjbs.2008.900.904
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic Transmission of Rice yellow mottle virus Through Soil and Contact Between Plants

Abstract: The roles of guttation fluid, irrigation water, contact between plants and transplantation into contaminated soil in the transmission of Rice yellow mottle virus (RYMV) were assessed. RYMV presence and infectivity were tested by Enzyme-Linked Immunosorbent Assay (ELISA) and by inoculation to susceptible rice cultivar BG90-2. The virus was readily detected in guttation fluid collected from infected rice plants. Transmission tests from this fluid led to high disease incidence (86.6%). Irrigation water collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Up to 44% healthy rice plants in contact with RYMVinfected plants became infected (Traoré et al, 2008). This virus is also transmitted abiotically by cows, donkeys, and grass rats (Sarra and Peters, 2003), through guttation fluid (Section VII, G), by beetles (Section III, K), and through contaminated soil, but not through roots (Traoré et al, 2008).…”
Section: Abiotic Transmission Above Groundmentioning
confidence: 99%
“…Up to 44% healthy rice plants in contact with RYMVinfected plants became infected (Traoré et al, 2008). This virus is also transmitted abiotically by cows, donkeys, and grass rats (Sarra and Peters, 2003), through guttation fluid (Section VII, G), by beetles (Section III, K), and through contaminated soil, but not through roots (Traoré et al, 2008).…”
Section: Abiotic Transmission Above Groundmentioning
confidence: 99%
“…RYMV belongs to the Sobemovirus group and is transmitted either mechanically (Bakker 1974;Fauquet and Thouvenel 1977), several insects or various mammals (Traor e et al 2009). Transmission from leaf to leaf, irrigation water next to infected plants, infected soil (Traor e et al 2008), cow dung or soil with insufficiently decomposed affected plant debris (Reckhaus and Andriamasintseheno 1995) has been documented. Transmission from leaf to leaf, irrigation water next to infected plants, infected soil (Traor e et al 2008), cow dung or soil with insufficiently decomposed affected plant debris (Reckhaus and Andriamasintseheno 1995) has been documented.…”
Section: Introductionmentioning
confidence: 99%
“…Appropriate management of ratoons that can cause soil and water contamination in heavily affected fields will be important for RYMV control. Transmission via soil contaminated with RYMV-leaves was shown to be positive by Traoré and Traoré (2008). The results of our soil transmission experiments indicated that roots, ratoons, and debris of RYMV-infected seedlings after harvesting can be a source of RYMV via contact and contamination of soil and water.…”
Section: Discussionmentioning
confidence: 73%
“…The virus is transmissible by animals, by wind-mediated leaf contact, and by abiotic factors (e.g. irrigation water) (Abo et al 2000;Sarra and Peters 2003;Sarra et al 2004;Traoré and Traoré 2008). Infection via farm equipment has also been confirmed (Sarra 2005).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation